Dependences of livelihoods on animal genetic resource (AnGR) - Assefa, Hailu (International Journal For Research In Agricultural And Food Science, 2019)
Animal genetic resources (AnGR) encompass all the animal species, breeds and strains that are used now, as well as in the past and in the future - by humans for the purpose of food production and agriculture. Livestock play important roles in the production of food and for other purposes. The diversified use of livestock contributes valuable gross domestic product (GDP), critical to world food security in general and providing considerable global protein consumption. Significant percent of the world’s rural poor depend on livestock for their livelihood. Livestock therefore are of great socio-economic and cultural value in various societies around the world. AnGR form the basis and the building blocks of the global livestock economy, a sector that is currently valued at income source, employs significant number of people and is essential to the livelihoods of poor small-scale livestock keepers. To utilize valuable resources from AnGR the potential of indigenous breeds in developing countries is often inadequately documented and utilized. Similarly there is a great challenge to alleviate poverty in developing countries by producing more and safe food, especially of animal origin, against a shrinking animal genetic diversity and increased global trade. Global initiatives must be locally internalized and accompanied by local activities to implement conservation programs that increase animal productivity while maintaining the necessary genetic diversity. Demonstrate effective breeding strategies (which take into account environmental, socio-economic and infrastructure constraints) must be developed. Research and capacity building at all levels to improve the knowledge of indigenous and alternative AnGR in different regions of the developing world is required. Summarizing and proposing initiatives for this situation and implications for the future use of AnGR is deed important.